1999
DOI: 10.1001/archpsyc.56.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Relapse Following Response From a First Episode of Schizophrenia or Schizoaffective Disorder

Abstract: Background:We examined relapse after response to a first episode of schizophrenia or schizoaffective disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

42
875
6
36

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,236 publications
(963 citation statements)
references
References 37 publications
42
875
6
36
Order By: Relevance
“…It remains, however, unknown whether these patients are treatment resistant from the illness onset (TRO), or whether they gradually become resistant as illness progresses in the context of multiple episodes, chronic exposure to medication or neurochemical sensitization. We have previously demonstrated that dopamine dysfunction is not evident in treatment-resistant patients (Demjaha et al 2012(Demjaha et al , 2014 and this, together with the evidence linking various underlying neurodevelopmental factors to treatment resistance (McCreadie et al 1989;Robinson et al 1999), may suggest that in this distinct subgroup, dopamine-blocking antipsychotics are ineffective right from the beginning of illness. In support of this, first-episode psychosis (FEP) studies have established that even during the first episode of illness where treatment response to antipsychotic medication tends to be greater; up to one-quarter of patients continue to have persistent symptoms despite adequate treatment (Lieberman et al 1993;Agid et al 2011;Schennach et al 2012).…”
Section: Introductionmentioning
confidence: 93%
“…It remains, however, unknown whether these patients are treatment resistant from the illness onset (TRO), or whether they gradually become resistant as illness progresses in the context of multiple episodes, chronic exposure to medication or neurochemical sensitization. We have previously demonstrated that dopamine dysfunction is not evident in treatment-resistant patients (Demjaha et al 2012(Demjaha et al , 2014 and this, together with the evidence linking various underlying neurodevelopmental factors to treatment resistance (McCreadie et al 1989;Robinson et al 1999), may suggest that in this distinct subgroup, dopamine-blocking antipsychotics are ineffective right from the beginning of illness. In support of this, first-episode psychosis (FEP) studies have established that even during the first episode of illness where treatment response to antipsychotic medication tends to be greater; up to one-quarter of patients continue to have persistent symptoms despite adequate treatment (Lieberman et al 1993;Agid et al 2011;Schennach et al 2012).…”
Section: Introductionmentioning
confidence: 93%
“…Recent reviews suggest that approximately 30% of patients eventually disengage from care (Kreyenbuhl et al, 2009;O'Brien et al, 2009). The problem is particularly severe for patients experiencing a first-episode of psychosis (FEP), where early disengagement is associated with poor patient outcomes (Robinson et al 1999(Robinson et al , 2002Ruggeri et al 2007;Schimmelmann et al 2006;Turner et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This suggests that factors other than treatment are associated with admission to hospital with a psychotic relapse. For example, numerous factors have been found to be associated with relapse including early adolescent adjustment (Robinson et al 1999), duration of untreated psychosis (Crow et al 1986), non-adherence with medication (Kemp et al 1998), expressed emotion (Kavanagh, 1992) and coping style (Hultman et al 1997). In addition, there is evidence to suggest that patients themselves monitor and regulate their symptoms in order to prevent relapse (Breier & Strauss, 1983;McCandless-Glimcher et al 1986 ;Hultman et al 1997).…”
mentioning
confidence: 99%